Effect of hypoglycemic agents on survival outcomes of lung cancer patients with diabetes mellitus: A meta-analysis. Issue 9 (March 2018) - Xin, Wen-Xiu; Fang, Luo; Fang, Qi-Lu; Zheng, Xiao-Wei; Ding, Hai-Ying; Huang, Ping
Abstract: Background: To assess the association between hypoglycemic agents and prognosis of lung cancer patients with diabetes. Methods: A comprehensive literature search was performed in PubMed, Web of Science, Embase, and Cochrane Library until May 2017. The search yielded 2593 unique citations, of which 18 articles met inclusion criteria. The hazard ratios (HRs) and 95% confidence intervals (95% CIs) were calculated by a fixed-effects or random-effects model. Results: The pooled HRs favoring metformin users were 0.77 for overall survival (OS) (n = 15, 95% CI: 0.68–0.86) and 0.50 for disease-free survival (n = 5, 95% CI: 0.39–0.64). One study assessed the relationship between metformin and cancer-specific survival (CSS), reporting no significant results. No significant association between insulin and OS (n = 2, HR: 0.95, 95% CI: 0.79–1.13) or CSS (n = 2, HR: 1.03, 95% CI: 0.76–1.41) was noted. One study evaluated association of sulfonylureas with lung cancer survival and reported no clinical benefit (HR: 1.10, 95% CI: 0.87–1.40). One study reported no association of thiazolidinediones with lung cancer survival (HR: 1.04, 95% CI: 0.65–1.66). Conclusions: This meta-analysis demonstrated that metformin exposure might improve survival outcomes in lung cancer patients with diabetes.